Mengukur Tingkat Pertumbuhan Badan Layanan Umum (BLU) Dengan Alat Penilaian Dan Evaluasi Maturity Rating - Repa Hudan Lisalam; Ilham Hibatullah; Mila Ayu Ardiani; Jesi Winarni; Sanawi Sanawi; Yani Aguspriyani; Trisna Taufik Darmawansyah (Universitas Islam Negeri Sumatera Utara, 2025)
This study explains how to Measure the Growth Rate of Public Service Agencies (BLU) from the Financial Aspect within a five-year period. The method used in this study is a quantitative method by analyzing the annual financial reports of Public Service Agencies (BLU). The object of this study is the Public Service Agency (BLU) of the education cluster, namely BLU UIN Sultan Maulana Hasanuddin Banten. The results of the study conducted at BLU UIN SMH Banten showed a very good liquidity aspect in terms of the current ratio. While the liquidity aspect of the cash optimization ratio is still low. The BLU Efficiency Aspect refers to the ratio of Operating Income to Operating Expenses (POBO), based on the results of calculations processed from the financial statements of BLU UIN Sultan Maulana Hasanuddin Banten from 2017 to 2022, there is no POBO value that reaches the target (90%). The BLU effectiveness indicator refers to Return On Asset (ROA) and Return on Equity (ROE), the target for each ratio is 9% and has generally been met. The level of independence generally shows a downward trend. Recommendations for finding short-term investment instruments with higher returns. Increasing Efficiency by reducing the burden of official travel. Managing Campus Assets optimally to increase the level of BLU independence. The analysis used is a combination of Financial Report Trend Analysis and Maturity Rating Assessment Tools and Evaluation Version 1.0.